Diversity of Bacillus-like organisms isolated from deep-sea hypersaline anoxic sediments - Sass, Andrea M (BioMed Central, 2008)
BACKGROUND: The deep-sea, hypersaline anoxic brine lakes in the Mediterranean are among the most extreme environments on earth, and in one of them, the MgCl(2)-rich Discovery basin, the presence of active microbes is equivocal. However, thriving microbial communities have been detected especially in the chemocline between deep seawater and three NaCl-rich brine lakes, l'Atalante, Bannock and Urania. By contrast, the microbiota of these brine-lake sediments remains largely unexplored. RESULTS: Eighty nine isolates were obtained from the sediments of four deep-sea, hypersaline anoxic brine lakes in the Eastern Mediterranean Sea: l'Atalante, Bannock, Discovery and Urania basins. This culture collection was dominated by representatives of the genus Bacillus and close relatives (90% of all isolates) that were investigated further. Physiological characterization of representative strains revealed large versatility with respect to enzyme activities or substrate utilization. Two third of the isolates did not grow at in-situ salinities and were presumably present as endospores. This is supported by high numbers of endospores in Bannock, Discovery and Urania basins ranging from 3.8 × 10(5 )to 1.2 × 10(6 )g(-1 )dw sediment. However, the remaining isolates were highly halotolerant growing at salinities of up to 30% NaCl. Some of the novel isolates affiliating with the genus Pontibacillus grew well under anoxic conditions in sulfidic medium by fermentation or anaerobic respiration using dimethylsulfoxide or trimethylamine N-oxide as electron acceptor. CONCLUSION: Some of the halophilic, facultatively anaerobic relatives of Bacillus appear well adapted to life in this hostile environment and suggest the presence of actively growing microbial communities in the NaCl-rich, deep-sea brine-lake sediments.